Routledge handbook of law and terrorism - Lennon, Genevieve; Walker, Clive (Routledge handbooks, 2015)
"In the years since 9/11 counter-terrorism law and policy has proliferated across the world. This handbook provides an authoritative and critical analysis of how laws are, and ought to be, invoked in domestic jurisdictions against terrorism. The original contributions to the book are written by experts in the field of terrorism law and policy, allowing for discussion of a wide range of regulatory responses and strategies of governance. The chapters engage with areas of traditional interest to lawyers such as policing, criminal offences, the courts, and prison regimes but also tackle emerging subjects including preventing radicalisation and protective/preparative security"--